2014
DOI: 10.1111/febs.12783
|View full text |Cite
|
Sign up to set email alerts
|

Diphtheria toxin conformational switching at acidic pH

Abstract: Diphtheria toxin (DT), the etiological agent of the homonymous disease, like other bacterial toxins, has to undergo a dramatic structural change in order to be internalized into the cytosol, where it finally performs its function. The molecular mechanism of toxin transit across the membrane is not well known, but the available experimental evidence indicates that one of the three domains of the toxin, called the central a-helical domain, inserts into the lipid bilayer, so favoring the translocation of the cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 40 publications
(63 reference statements)
1
32
1
Order By: Relevance
“…The finding that one SV contains one or two molecules of BoNT/A1 leaves open the possibility that one toxin molecule is sufficient to carry out the process and suggests that these toxins may have an in-built membrane translocating system, similarly to the bacterial system SecY (Park and Rapoport, 2012). Diphtheria toxin, a bacterial toxin with a structural architecture similar to that of BoNTs, also has a translocating domain that is mainly α -helical, and the available evidence supports a single molecule process, with few transmembrane helices forming an ion channel (Finkelstein et al, 2000; Gordon and Finkelstein, 2001; Leka et al, 2014). At variance, it was recently reported that a trimer might form the protein conducting transmembrane channel of BoNT/B1 in PC12 cells and BoNT/E1 at physiologic pH (Sun et al, 2012).…”
Section: Biologymentioning
confidence: 99%
“…The finding that one SV contains one or two molecules of BoNT/A1 leaves open the possibility that one toxin molecule is sufficient to carry out the process and suggests that these toxins may have an in-built membrane translocating system, similarly to the bacterial system SecY (Park and Rapoport, 2012). Diphtheria toxin, a bacterial toxin with a structural architecture similar to that of BoNTs, also has a translocating domain that is mainly α -helical, and the available evidence supports a single molecule process, with few transmembrane helices forming an ion channel (Finkelstein et al, 2000; Gordon and Finkelstein, 2001; Leka et al, 2014). At variance, it was recently reported that a trimer might form the protein conducting transmembrane channel of BoNT/B1 in PC12 cells and BoNT/E1 at physiologic pH (Sun et al, 2012).…”
Section: Biologymentioning
confidence: 99%
“…These features were interpreted as initial stages of formation of a membrane competent state of the T-domain in solution (Flores-Canales et al; Kurnikov et al, 2013). Recent X-ray structures of diphtheria toxin distressed by exposure to low pH prior to crystallization process at neutral pH (Leka et al, 2014) have also indicated the possibility of refolding of the N-terminal helices as predicted by (Kurnikov et al, 2013). …”
Section: Introductionmentioning
confidence: 99%
“…DTA is transported from the luminal side of endosomal membranes to the cytosolic side and this translocation step from early acidified endosomes into the cytosol is the last step during the cellular uptake of the toxin 16–18 . This step is fostered by the T-domain, which forms a pore in the endosomal membrane 19–21 and thereby mediates trans-membrane transport of unfolded DTA 2226 . During or after the trans-membrane transport the DTA is released from the DTB by reduction of the disulfide bond by the thioredoxin reductase/thioredoxin system of host cells 6, 16, 27, 28 .…”
Section: Introductionmentioning
confidence: 99%